ADDRESSING THE POLICE PREJUDICE IN BANGLADESH: A SECONDARY ANALYSIS - Mohiuddin, Pro. Anira Mohiuddin (International Journal of Multidisciplinary Research and Studies, 2021)
Police prejudice is widespread in many countries, but relatively new in Bangladesh. It means favor to a certain group while giving unfair treatment to other groups. Thus, the study revealed the present picture of prejudice, process and factors, some parameters such as victim and area of prejudice, and the steps to fight against prejudice. Using secondary literature for analysis this study has found that the main victims are marginalized, poor and indigenous people who faced prejudice while lodging cases or during the investigation. The culture of impunity and politics had a great effect on the influence of prejudice. Police prejudice often sheds as a violation of human rights. It also added public perception about police prejudice and suggestions. This study finally recommends police use new strategies to reduce prejudice and offers suggestions for future research that sheds in-depth light on the link between prejudices among police officers.